Quantitative Susceptibility Mapping: Technical Considerations and Clinical Applications in Neuroimaging. Issue 1 (17th January 2020) - Vinayagamani, Selvadasan; Sheelakumari, R; Sabarish, Sekar; Senthilvelan, Santhakumar; Ros, Roopa; Thomas, Bejoy; Kesavadas, Chandrasekharan
Abstract : Quantitative susceptibility mapping (QSM) is a novel magnetic resonance imaging (MRI) technique for quantifying the spatial distribution of magnetic susceptibility within an object or tissue. Recently, QSM has been widely used to study various dominant magnetic susceptibility sources in the brain, including iron and calcium. In addition, the method enables mapping of the cerebral metabolic rate of oxygen, which could act as a new metabolic biomarker for diseases that involve disruption of the brain's oxygen supply. Thus, the clinical applications of QSM are wide‐reaching and hold great promise as imaging biomarkers for studying several neurological diseases. This review aims to summarize the physical concepts and potential clinical applications of QSM in neuroimaging. Evidence Level: 5 Technical Efficacy: Stage 2